2002
DOI: 10.1029/2001jd000510
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yields for production of O(1D) in the ultraviolet photolysis of ozone: Recommendation based on evaluation of laboratory data

Abstract: [1] The quantum yield for O( 1 D) production in the photolysis of ozone in the ultraviolet region as a function of wavelength and temperature is a key input for modeling calculations in the atmospheric chemistry. To provide the modeling community with the best possible information, the available data are critically evaluated, and the best possible recommendations for the quantum yields are presented. Since the authors of this paper are the principal investigators of the groups which have provided most of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 57 publications
(235 reference statements)
1
114
1
Order By: Relevance
“…The most re- Talukdar et al (1998). This is larger then the differences (< 2%) reported by Matsumi et al (2002), however, they reported differences for the surface while the differences reported here occur at altitudes above 13 km. As opposed to earlier figures the photodissociation rates are shown as a function of altitude in Fig.…”
Section: Photodissociation Ratescontrasting
confidence: 55%
See 1 more Smart Citation
“…The most re- Talukdar et al (1998). This is larger then the differences (< 2%) reported by Matsumi et al (2002), however, they reported differences for the surface while the differences reported here occur at altitudes above 13 km. As opposed to earlier figures the photodissociation rates are shown as a function of altitude in Fig.…”
Section: Photodissociation Ratescontrasting
confidence: 55%
“…10. The ozone cross section and quantum yields used to calculate J[O( 1 D)] were taken from Bass and Paur (1985) and Matsumi et al (2002) respectively, while the NO 2 cross section and quantum yields were taken from Davidson et al (1988) and DeMore et al (1994) respectively. The accuracy of the NO 2 cross sections are estimated to be ±5% (Davidson et al, 1988).…”
Section: Photodissociation Ratesmentioning
confidence: 99%
“…OH was generated by O 3 photolysis at 248 nm using an excimer laser operating on KrF (Lambda Physik, COMPEX 102), followed by reaction of the O( 1 D) photo-fragment (0.9 quantum yield 19 ) with CH 3 OH (R3) or H 2 (R4):…”
Section: Introductionmentioning
confidence: 99%
“…Temperature dependencies of σ values are included for 18 of the chosen chemical species (see Table 2). Moreover, a temperature dependency for the φ related to O 1 D production from the photolysis of O 3 was also included as recommended by Matsumi et al (2002). For the calculation of the Rayleigh scattering cross-sections the empirical approach of Nicolet (1984) is used.…”
Section: The Model Atmosphere and Spectroscopic Datamentioning
confidence: 99%
“…This arises from updating the method in which φ is determined (where the temperature dependent σ values originate from Molina and Molina (1986) in both cases). The original quantum yield was taken from the study of Talukdar et al (1998), whereas the one adopted here was based on the recommendation of Matsumi et al (2002), which is a critical synthesis of many independent studies. This update leads to substantial differences especially in the contribution made by the fourth band to J O 3 (→O 1 D) and, more importantly, the contribution to the total J value made by each wavelength bin (not shown).…”
Section: Selection Of the Band Limitsmentioning
confidence: 99%